2019
DOI: 10.1039/c9ra06551b
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and giant negative electrocaloric effect of a Nb and Sn co-doped lead zirconate titanate antiferroelectric film near room temperature

Abstract: A giant negative ECE of a PNZST film with a high electrocaloric coefficient and coefficient of performance near room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…To understand the main characteristics of field-induced phase transition of PNZST films deposited on different electrodes, all the coefficients are normalized and assumed to be T = 20°C, T 0 = 190°C, a 1 = 1, b = c = 1/3 and g = 0.5. 26,39 Through the thermodynamic equilibrium, ∂f AFE /∂P 1 = ∂f AFE /∂P 2 = ∂f FE /∂P 3 = 0, following relations could be established by According to Equations (4), (7), and (8), the free energies of AFE and FE phases under different applied electric fields are shown in Figure 5A,B. It is indicated that the minimum free energy of AFE phase shifts from P = 0 to approximate P = 1.81 suddenly when E is larger than 0.54.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To understand the main characteristics of field-induced phase transition of PNZST films deposited on different electrodes, all the coefficients are normalized and assumed to be T = 20°C, T 0 = 190°C, a 1 = 1, b = c = 1/3 and g = 0.5. 26,39 Through the thermodynamic equilibrium, ∂f AFE /∂P 1 = ∂f AFE /∂P 2 = ∂f FE /∂P 3 = 0, following relations could be established by According to Equations (4), (7), and (8), the free energies of AFE and FE phases under different applied electric fields are shown in Figure 5A,B. It is indicated that the minimum free energy of AFE phase shifts from P = 0 to approximate P = 1.81 suddenly when E is larger than 0.54.…”
Section: Resultsmentioning
confidence: 99%
“…The different energy storage properties of PNZST/LNO and PNZST/Pt films could be explained by a thermodynamic model of AFE and FE phase coexistence system. According to the Kittel model, the free energy of AFE phase, f AFE , can be described by the FE polarization order parameter p and AFE polarization order parameter q as following Equations 26,39 fAFE=14ap2+q2+132bfalse(p4+6p2q2+q4false)+1192cp6+15p4q2+15p2q4+q6+14gp2q2pE,p=P1+P2,q=P1P2,where P 1 and P 2 represent the polarization components for the two sub‐lattices 1 and 2, respectively. Here a , b , c are the Landau‐type expansion coefficients for each sub‐lattice, g is the AFE coupling strength and E is normalized applied electric field.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 21,22 ] Therefore, AFE films will exhibit a distinctly different stress‐induced polarization, and related thermal and electrical properties. [ 23–26 ] Up to now, these aspects still remain less understood, whether in theory or experiment.…”
Section: Introductionmentioning
confidence: 99%